Influence of Brand Image, Quality Products, And Prices Against Loyalty Customer Tiktok Shop With Satisfaction Customer As Intervening Variables ( Case Study of Students in Medan City) - Hasmanan Khair; Satria Tirtayasa; Utami Herawati (Cita konsultindo, 2024)
Study This aims to determine the influence of brand image, product quality, and price on Tiktok Shop customer loyalty, with customer satisfaction as an intervening variable among students in Medan. The approach used in the study This is an associative quantitative approach. The population in this study were Medan city students who had made purchases at the Tiktok Shop 2 or more times, the number of which is unknown. The sample for this research was 390 respondents. The data collection technique in this research used a questionnaire. Data analysis techniques using a quantitative approach using SEM PLS. Research results show that brand image, product quality, and customer satisfaction positively and significantly affect Tiktok Shop's customer loyalty. Brand image, product quality, and price positively and significantly affect Tiktok Shop's customer satisfaction. Meanwhile, price has no positive and insignificant effect on TikTok Shop customer loyalty. Brand image, product quality, and price positively and significantly affect Tiktok Shop customer loyalty through customer satisfaction among students in Medan